Topical fenticonazole in dermatology and gynaecology. current role in therapy - Стефано Веральді; Родольфо Мілані (Publishing House TRILIST, 2019)
The objective of this review is to present the current clinical data on the use of fenticonazole, including data on its efficacy in mixed infections, and to discuss the clinical role of fenticonazole in dermatological and gynaecological indications. Fenticonazole is an imidazole derivative with a broad spectrum of antimycotic activity against dermatophytes and yeasts in in vitro and clinical studies. Fenticonazole exerts its unique antimycotic mechanism of action in the following three ways: (I) inhibition of the secretion of protease acid by Candida albicans; (II) damage to the cytoplasmic membrane; (III) and by blocking cytochrome oxidases and peroxidises. Fenticonazole has also been shown to exhibit antibacterial action, with a spectrum of activity that includes bacteria commonly associated with superinfected fungal skin and vaginal infections, and antiparasitic action against the protozoan Trichomonas vaginalis. Therefore, fenticonazole may be an ideal topical alternative to multiagent treatment of mixed infections involving mycotic, bacterial, dermatophyte and/or Trichomonas spp. Intravaginal fenticonazole is at least as effective as clotrimazole and shows similar efficacy to miconazole in patients with vaginal candidiasis. Fenticonazole has a rapid onset of action and clinical efficacy is generally observed within days of commencing treatment. Intravaginal administration of fenticonazole is associated with a high rate of microbiological efficacy in patients with vaginal candidiasis, trichomoniasis, mixed infection and bacterial vaginosis. Fenticonazole has a rapid onset of action and clinical efficacy is generally observed within days of commencing treatment. Topical fenticonazole is very well tolerated; adverse events are generally mild to moderate in severity and transient. The most frequent adverse events are burning sensation/cutaneous irritation and itch when applied t ptom of vaginal fungal infection was often present in patients prior to drug administration. Given the rising incidence of superficial fungal, and possibly mixed, infections, topical fenticonazole represents an important part of the topical antimycotic armamentarium.